2022
DOI: 10.1021/acs.inorgchem.2c03190
|View full text |Cite
|
Sign up to set email alerts
|

Electron Counting and High-Pressure Phase Transformations in Metal Hexaborides

Abstract: Pressure-induced structural transitions of the alkaline earth hexaborides, CaB6, SrB6, and BaB6, are studied theoretically using electron counting rules and density functional theory calculations. We demonstrate the applicability of gas-phase borane electron counting methods to solid-state metal borides under pressure and validate the assumptions of the rules by density functional theory (DFT) calculations. All three compounds share ambient-pressure and high-pressure structures, but BaB6 differs from CaB6 and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…39,40 Solids containing cluster anions are particularly amenable to electron counting analysis -for example, the conductivities of metal hexaborides, MB 6 , can be predicted from the metal valence state by application of the Wade-Mingos rules. [41][42][43][44] In this study we focus on covalent sub-units in the H-H networks of LaH 10 , 11 EuH 9 , 37 and UH 8 , 45,46 all shown in Figure 1, in order to explain structural trends. LaH 10 is well-studied by theory and experiments, as described above.…”
Section: Introductionmentioning
confidence: 99%
“…39,40 Solids containing cluster anions are particularly amenable to electron counting analysis -for example, the conductivities of metal hexaborides, MB 6 , can be predicted from the metal valence state by application of the Wade-Mingos rules. [41][42][43][44] In this study we focus on covalent sub-units in the H-H networks of LaH 10 , 11 EuH 9 , 37 and UH 8 , 45,46 all shown in Figure 1, in order to explain structural trends. LaH 10 is well-studied by theory and experiments, as described above.…”
Section: Introductionmentioning
confidence: 99%
“…39,40 Solids containing cluster anions are particularly amenable to electron counting analysis – for example, the conductivities of metal hexaborides, MB 6 , can be predicted from the metal valence state by application of the Wade–Mingos rules. 41–44…”
Section: Introductionmentioning
confidence: 99%
“…39,40 Solids containing cluster anions are particularly amenable to electron counting analysisfor example, the conductivities of metal hexaborides, MB 6 , can be predicted from the metal valence state by application of the Wade-Mingos rules. [41][42][43][44] In this study we focus on covalently bonded hydrogen clusters in LaH 10 , 11 EuH 9 , 37 and UH 8 , 45,46 all shown in Fig. 1, in order to explain structural trends.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the hexaborides of the CaB 6 type are refractory compounds with high melting temperatures (above 2600 °C for YB 6 ); they are characterized by excellent acid and oxidation resistance at high temperature and high hardness and high bulk moduli. In recent years, a large number of experimental and theoretical research focused on studying the properties of hexaborides under pressure, revealing the rich chemistry of B in the high pressure polymorphs of hexaborides. , Several supercells with reduced symmetry for YB 6 have been claimed to exist at ambient conditions [both from experimental studies (Raman spectroscopy) and DFT calculations] and have been suggested to be more stable than the commonly accepted CaB 6 -type structure. …”
Section: Introductionmentioning
confidence: 99%